Estudo dos determinantes da insegurança alimentar em pacientes atendidos em um serviço de assistência especializada em HIV/AIDS - Cozer, Mirian (2016)
People living with HIV/Aids are generally a vulnerable group in many aspects: socially, economically and/or regarding health issues. Therefore, food and nutrition insecurity might be a recurring problem. Our research aims to determine insecurity prevalence concerning this group of people who are treated in Francisco Beltrão/PR Specialized Assistance Service (SAS). This dissertation is described as a cross-sectional study, with data collection from a questionnaire. The analysis was carried out through quantitative and qualitative methodologies and a statistics software that was used in order to develop our descriptive stats: frequency calculus, rate and standard deviation. As for comparisons between proportions we employed Yates's or Fischer's chi-square test, correcting 2x2 charts. Results were considered statistically meaningful on p<0,05 level. 126 individuals living with HIV/Aids were participants on the research. These people are treated in the SAS, they are all over 18 and under 60 years old. They underwent a questionnaire with questions ranging from social to economic and health aspects of their lifes. After that they went through anthropometric evaluation and an individual interview with the researcher. Our aim there was to determine their food and nutrition insecurity levels through the Brazilian Food and Nutrition Insecurity Scale (EBIA). 61,9% (N=78) of the interviewees faced food and nutrition insecurity in some level, the prevalence was of 16,7%: 9,7% with small insecurity; 4,9% with moderate insecurity and 2,1% with major insecurity. This condition is more significant in individuals who have less than three minimum wages worth of income, according to the following odds ratio (OR): 0,151 (0,0644 - 0,3544), odds ratio (OR): 0,2174 (0,0468 - 1,0099). 74,45% of those who suffer from this condition live with up to three minimum wages worth of income (R$2.376,00). When analysing non communicable chronic diseases we checked that patients with one NCCD or more were under greater risk of suffering from food and nutrition insecurity, however, not meaningful regarding p<0,05. Concerning the patients nutritional situation there were more eutrophic ones for the body mass index (BMI) and arm circunference (AC) evaluation parameters. According to the theoretical model for food and nutritional insecurity we could see that, on the triad that assumes distal risk factors as social, demographic and economic attributes were meaninful. We emphasize that these variables can directly act on food and nutritional insecurity, the third distal risk factor might be affected by it (demographic attribute), causing insecurity to happen. 63% (N=70) from the participants under insecurity have CD4 cell count over 200/mm3 and 62% (N=56) viral load below 40 copies/ml, which indicates that HIV/Aids presence is not a decisive factor for insecurity in contrast to food habits and life quality, which are usually decisive for causing it. Alongside it 66% (N=52) from the non-safe participants have habits such as drinking alcohol, which is another life quality decisive factor. According to the obtained results it is possible to affirm that the disease compromises the individual in his/her working potential, which causes him/her to be more susceptible to food and nutrition insecurity, and this can be seen as an inequality cause concerning the economic system once poverty and inequality are decisive factors for food and nutrition insecurity and, for that reason, its estimates can be used, as a complementary factor, in order to identify biases and driving factors for regional development as a whole.